2021
DOI: 10.1186/s13287-021-02410-w
|View full text |Cite
|
Sign up to set email alerts
|

Adipose-derived mesenchymal stromal cell-derived exosomes promote tendon healing by activating both SMAD1/5/9 and SMAD2/3

Abstract: Background The use of adipose-derived mesenchymal stromal cell-derived exosomes (ADSC-Exos) may become a new therapeutic method in biomedicine owing to their important role in regenerative medicine. However, the role of ADSC-Exos in tendon repair has not yet been evaluated. Therefore, we aimed to clarify the healing effects of ADSC-Exos on tendon injury. Methods The adipose-derived mesenchymal stromal cells (ADSCs) and tendon stem cells (TSCs) were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
85
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(87 citation statements)
references
References 48 publications
2
85
0
Order By: Relevance
“…Besides, ADSC exosomes have also been found to activate the SMAD signaling pathway in tendon healing ( Liu et al, 2021a ), which is consistent with the above findings that SMAD transduction is upregulated by BMSC and USC exosomes. Thus, further analysis should be expanded about the SMAD signaling pathway via ADSC exosomes in the treatment of IDD, and the correlations between SMAD and other different sources of exosomes should also be further observed.…”
Section: Potential Sources Of Applications By Exosomes During the Pro...supporting
confidence: 86%
“…Besides, ADSC exosomes have also been found to activate the SMAD signaling pathway in tendon healing ( Liu et al, 2021a ), which is consistent with the above findings that SMAD transduction is upregulated by BMSC and USC exosomes. Thus, further analysis should be expanded about the SMAD signaling pathway via ADSC exosomes in the treatment of IDD, and the correlations between SMAD and other different sources of exosomes should also be further observed.…”
Section: Potential Sources Of Applications By Exosomes During the Pro...supporting
confidence: 86%
“…During extrinsic healing, inflammatory cells and fibroblasts migrate from surrounding tissues, such as the sheath and synovium, to react in the initial inflammatory phase in the healing process [ 52 , 53 ]. Growth factors and cytokines released by the inflammatory cells during the initial phase play a dominant role in directing stem cell differentiation, tenocyte proliferation, and neo-tendon maturation in the later proliferative and regenerative phase [ 54 , 55 , 56 , 57 ]. Existing studies have shown encouraging anti-inflammatory and anti-scarring properties of exosomes in extrinsic healing of tendons.…”
Section: Exosomes In Tendon and Repair And Regenerationmentioning
confidence: 99%
“…Existing studies have shown encouraging anti-inflammatory and anti-scarring properties of exosomes in extrinsic healing of tendons. One of the most well-recognized mechanisms of exosomes is their capability of facilitating macrophage polarization and maintaining a dominant M2 pattern via paracrine [ 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 ].…”
Section: Exosomes In Tendon and Repair And Regenerationmentioning
confidence: 99%
“…Transplantation of BM-MSC-derived EVs promotes tendon healing in rat model AT in a dose-dependent manner with the organization of tendon fibers, architecture, and type 1 collagen [ 137 ]. AD-MSC-derived Exos enhance tenogenic differentiation of TSCs and reduce inflammation through SMAD2/3 and SMAD1/5/9 signaling pathways [ 138 ]. AD-MSC-derived Exos enhance the proliferation of CD146 + TSCs.…”
Section: Orthobiologics In Atmentioning
confidence: 99%